2020
DOI: 10.7150/ijbs.48330
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome in IgA Nephropathy: State-of-Art and Future Perspectives

Abstract: IgA nephropathy (IgAN) is a leading cause of chronic kidney disease and renal failure. The exact pathogenesis of IgAN is not well defined, but some genetic studies have led to a novel discovery that the immunoproteasome probably plays an important role in IgAN. The immunoproteasome is a proteasome variant that is expressed when cells are stressed or receive inflammatory signals. While immunoproteasome is suggested to be mainly involved in major histocompatibility complex-I (MHC-I) antigen presentation, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…The trace of NF-κB in IgAN pathogenicity has been previously shown, where toll-like receptors trigger a cascade of intracellular messages that finally leads to the activation of this transcription regulator [47]. The consequence of such activation is the cellular release of different cytokines and chemokines, which may participate in aberrant galactosylation of IgA1 [48].…”
Section: Discussionmentioning
confidence: 93%
“…The trace of NF-κB in IgAN pathogenicity has been previously shown, where toll-like receptors trigger a cascade of intracellular messages that finally leads to the activation of this transcription regulator [47]. The consequence of such activation is the cellular release of different cytokines and chemokines, which may participate in aberrant galactosylation of IgA1 [48].…”
Section: Discussionmentioning
confidence: 93%
“…The trace of NF-κB in IgAN pathogenicity has been previously shown, where Toll-like receptors trigger a cascade of intracellular massages that nally leads to the activation of this transcription regulator [43]. The consequence of such activation is cellular release of different cytokines and chemokines, which may participate in aberrant galactosylation of IgA1 [44].…”
Section: Discussionmentioning
confidence: 93%
“…According to the findings, the ac-tivities of several members of the ubiquitin-proteasome system involving in ubiquitination and proteasome degradation processes, respectively, are enhanced in IgAN, leading to the abnormal function of the ubiquitinproteasome regulatory pathway, which may be relate to the pathogenesis of IgAN. Some genetic studies have provided clues that proteasomes may be involved in the pathogenesis of IgAN [1,2]. Coppo et al [1] observed an upregulation of the immunoproteasome as well as a switch from proteasome to immunoproteasome with higher catalytic efficiency in PBMCs of IgAN patients.…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy (IgAN) is a leading cause of chronic kidney disease and end-stage renal disease. The exact pathogenesis of IgAN is not well defined, but some genetic studies have led to a novel discovery that the (immuno)proteasome probably plays an important role in IgAN [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%